PENDIDIK DALAM BERBAGAI DIMENSI (Teologis, Biologis, Psikologis dan Sosiologis) - M. Anshari; Husin Husin (ADDABANA: Jurnal Pendidikan Agama Islam, 2019)
Islamic terminology to know the term educator with the word al-murabbi, al-mu'addib and al-mu'allim. There is no contradiction between the sharp third term, but a third of those words indicate the construction of the physical (jasmaniyah) and (ruhiyyah). To explore the meaning of this research theme researchers use research library research with deductive patterns of thought and analyzed in content analysis. Research findings show that the dimension of educators consisting of the elements of the physical and psychic, both are one of the factors in the formation of attitude and character, the physical-biological human beings have in common, and the same tendency between one and the other, in the human psychic have in common but different tendencies, so that education not only in the formation of physical but more importantly, is the formation of psychic protege. Keywords: Islamic Theological Educator, Antroposenteris.